GENERALIZING THE INFORMATION REGARDING CHLAMYDIAL INFECTIONS AND THEIR ZOONOTIC POTENTIAL - Zezekalo, V.; Peredera, S.; Shcherbakova, N. (Scientific Progress & Innovations, 2019)
The aim of this paper is to provide updated and generalized the information regarding chlamydial infec-tions in both domestic and wild animal species, with an emphasis on the diseases that are caused by certain species of chlamydia and its zoonotic potential, and also to explain regarding the host range expansion for various types of chlamydia and chlamydia-related organisms. The following research methods were used: system analysis of available scientific sources, empirical method (according to a comprehensive assessment of the current state of the research object), abstract-logical − to clarify the essence of the basic concepts. Chlamydiae are extremely widespread around the world; they cause a wide range of diseases of various or-gans and systems. Chlamydiae cover a broad host range: protozoa, arthropods, fish, birds, wild animals, livestock, domestic animals, humans, and so on. Chlamydiae adapt well and multiply in the epithelial cells of the mucous membranes of the respiratory system, urogenital system, digestive tract organs, and in the cells of the reticulo-endothelial system. The nature of the pathological changes caused by chlamydiae depends on the types of chlamydias, their tropism and the route of infection. The broad host range that can be infected and the variety of clinical manifestations make it difficult to standardize diagnostic approaches for these pathogens. There is an increase in the host range for the known species, and new species are emerging that pose a threat to animal and human health. The number of species that pose a potential zoonotic threat has increased, and pet owners, agricultural workers and other people who have direct contact with animals should take this into account. The updated and generalized information on chlamydial infections of both do-mestic and wild animal species is presented, with an emphasis on diseases, which are caused by certain types of chlamydiae and their zoonotic potential. Explanations are given regarding the host range expansion for various types of chlamydiae and chlamydia-related organisms. The information provided can be used in scientific research, introduced into the educational process in the field of veterinary medicine, and can also be used by practicing veterinary doctors in order to improve the treatment and prevention of animal and human chlamydioses.